2015
DOI: 10.1063/1.4930878
|View full text |Cite
|
Sign up to set email alerts
|

Secondary resonance magnetic force microscopy using an external magnetic field for characterization of magnetic thin films

Abstract: A bimodal magnetic force microscopy (MFM) that uses an external magnetic field for the detection and imaging of magnetic thin films is developed. By applying the external modulation magnetic field, the vibration of a cantilever probe is excited by its magnetic tip at its higher eigenmode. Using magnetic nanoparticle samples, the capacity of the technique which allows single-pass imaging of topography and magnetic forces is demonstrated. For the detection of magnetic properties of thin film materials, its signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This technique has also been combined with the use of an external magnetic field to excite the magnetic tip of the probe to detect various magnetic materials. It was demonstrated that its sensitivity and signalto-noise ratio were superior to conventional MFM techniques [14]. In both studies, it was observed that this technique also had increased spatial resolution when the tip was closer to the sample surface [12,14].…”
Section: Magnetic Force Microscopy For Nanoparticle Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…This technique has also been combined with the use of an external magnetic field to excite the magnetic tip of the probe to detect various magnetic materials. It was demonstrated that its sensitivity and signalto-noise ratio were superior to conventional MFM techniques [14]. In both studies, it was observed that this technique also had increased spatial resolution when the tip was closer to the sample surface [12,14].…”
Section: Magnetic Force Microscopy For Nanoparticle Characterizationmentioning
confidence: 96%
“…It was demonstrated that its sensitivity and signalto-noise ratio were superior to conventional MFM techniques [14]. In both studies, it was observed that this technique also had increased spatial resolution when the tip was closer to the sample surface [12,14].…”
Section: Magnetic Force Microscopy For Nanoparticle Characterizationmentioning
confidence: 96%
“…When the MFM probe is brought close to the sample and is exposed to the external magnetic field, the oscillation amplitude (A) and the phase shift (Δ) are altered as shown in equation (2) and (3), respectively [9]:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Among these methods, the modulation method shows advantages for extracting magnetic force signals and increasing force sensitivity near the sample surface. For example, Liu et al (2015) [22] developed secondary resonance MFM (SR-MFM) for imaging the weak magnetism in magnetic thin films by exciting the vibration of a cobalt-coated cantilever probe to its higher eigenmode with an external AC magnetic field. Similarly, Li et al (2016) [23] introduced an AC field modulated MFM technique, which uses the frequency modulation of a cantilever oscillation by applying an AC magnetic field to a mechanically oscillated high-coercivity FePt tip, to locally characterize the magnetic behavior of individual magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%